From Independence Day to Land of Plenty: Screening American Patriotism from German Émigré Perspectives before and after 9/11 - Frank Mehring (European Journal of American Studies)
Independence Day and Land of Plenty are two tropes referring to the basis of American national identity: the Declaration of Independence with its guarantee of equal and inalienable rights and the promise of an inexhaustible abundance of resources. Independence Day and Land of Plenty are also two American feature films directed by German émigrés, the first being a science fiction blockbuster from 1996 by Roland Emmerich, the second an independent road movie from 2003 by Wim Wenders. Both films confront the issue of American patriotism albeit from different angles and at different times. Independence Day wholeheartedly embraces the American founding myths and translates them into a science fiction scenario. Wenders manoeuvres into an artistic space producing what I call patriotism of dissent. The films engage in a kind of dialectic dialogue on American patriotism. This article takes a close look at émigré perspectives on American patriotism before and after 9/11. By turning to the four patterns which political theorist Samuel P. Huntington identified as possible responses to the discrepancy between principles and practices of American democracy, I will analyse Independence Day as a filmic strategy to deny democratic gaps and Land of Plenty as a representative example of a moralistic reaction to democratic gaps. In the discourse of screening American patriotism from German émigré perspectives before and after 9/11, the work of Emmerich and Wenders exemplifies the spectrum of approaches to negotiate the fantasy of, desire for, and experience of American culture in the medium of film.